2021
DOI: 10.1021/acs.inorgchem.1c00762
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Photodynamic Studies on Nitrosylruthenium-Complexed Serum Albumin as a Delivery System for Controlled Nitric Oxide Release

Abstract: How to deliver nitric oxide (NO) to a physiological target and control its release quantitatively is a key issue for biomedical applications. Here, a water-soluble nitrosylruthenium complex, [(CH3)4N]­[RuCl3(5cqn)­(NO)] (H5cqn = 5-chloro-8-quinoline), was synthesized, and its structure was confirmed with 1H NMR and X-ray crystal diffraction. Photoinduced NO release was investigated with time-resolved Fourier transform infrared and electron paramagnetic resonance (EPR) spectroscopies. The binding constant of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Tunability of the structure of MOFs, reviewed by Seabra and Duran, also allows for controlled release of NO for specific biological applications . Finally, many ls-{RuNO} 6 and ls-{MnNO} 6 complexes have shown utility as light-triggered NO delivery platforms for photodynamic therapy. ,,, …”
Section: Nitric Oxide In Mammalian Signaling and Immune Defensementioning
confidence: 99%
“…Tunability of the structure of MOFs, reviewed by Seabra and Duran, also allows for controlled release of NO for specific biological applications . Finally, many ls-{RuNO} 6 and ls-{MnNO} 6 complexes have shown utility as light-triggered NO delivery platforms for photodynamic therapy. ,,, …”
Section: Nitric Oxide In Mammalian Signaling and Immune Defensementioning
confidence: 99%
“…The HSA molecule is a single-chain protein which contains 585 amino acid residues in a heart-like shape, and the three domains in HSA provide binding sites for a wide variety of endogenous ligands ( Ghuman et al, 2005 ; Xie et al, 2021 ). To examine the number of the Fe complex bound to HSA in solution, the native and Fe complex–treated HSA were analyzed by MALDI-TOF MS.…”
Section: Resultsmentioning
confidence: 99%
“…16, PDB ID: ). 63,208,209 It should be noted that two other structures of HSA adducts with ruthenium complexes were also reported, namely HSA-[RuCl 5 (indazole)] 2− , 208 and HSA-[RuCl 4 (indazole) 2 ] − . 209…”
Section: Ruthenium Nitrosyl Complexes As Potential Anticancer Drugsmentioning
confidence: 88%
“…16, PDB ID: 7DL4). 63,208,209 It should be noted that two other structures of HSA adducts with ruthenium complexes were also reported, namely HSA-[RuCl 5 (indazole)] 2− , 208 and HSA-[RuCl 4 (indazole) 2 ] − . 209 The investigation of the photoinduced inactivation of DNA repair enzymes (DNA glycosylases) in vitro by [RuNO(L) 2 (NO 2 ) 2 OH], where L = 3-methylpyridine, 210 revealed that the activity of DNA glycosylases decreased by more than 90% after irradiation.…”
Section: Dalton Transactions Perspectivementioning
confidence: 92%
See 1 more Smart Citation